Protein coding potential of retroviruses and other transposable elements in vertebrate genomes - Zdobnov, Evgeny M. (Oxford University Press, 2005)
We suggest an annotation strategy for genes encoded by retroviruses and transposable elements (RETRA genes) based on a set of marker protein domains. Usually RETRA genes are masked in vertebrate genomes prior to the application of automated gene prediction pipelines under the assumption that they provide no selective advantage to the host. Yet, we show that about 1000 genes in four vertebrate gene sets analyzed contain at least one RETRA gene marker domain. Using the conservation of genomic neighborhood (synteny), we were able to discriminate between RETRA genes with putative functionality in the vertebrates and those that probably function only in the context of mobile elements. We identified 35 such genes in human, along with their corresponding mouse and rat orthologs; which included almost all known human genes with similarity to mobile elements. The results also imply that the vast majority of the remaining RETRA genes in current gene sets are unlikely to encode vertebrate functions. To automatically annotate RETRA genes in other vertebrate genomes, we provide as a tool a set of marker protein domains and a manually refined list of domesticated or ancestral RETRA genes for rescuing genes with vertebrate functions.